Analisis Kebutuhan Kapasitor Bank Untuk Memperbaiki Faktor Daya Pada Gardu Induk Garuda Sakti 150 KV - Anto, Anto; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Along with the growth of society and the improvement of technology, the need for electric power continues to increase. However, the development of the electric power system is not sufficient to supply the required electrical energy needs. For this reason, it is necessary to regulate and manage a good electricity distribution system so that the current growing needs of the community are met and have high reliability. Installation failure in the electric power system cannot be avoided because the distance between the generator and the substation is very far, this causes the voltage on the receiving side to decrease. To increase the voltage and power factor it is necessary to install a capacitor bank. Capacitor bank installed in parallel to the substation load. The results of research and simulation of Matlab Simulink capacitor bank condition 2 × 25 MVAr with output voltage is 146 kV, current is 470 A and power factor is 0.93 lagging. After analyzing the need for a capacitor bank to achieve a lagging factor value of 0.95. the method used is the method of calculating the need for a capacitor bank to increase the power factor to 0.95 lagging. After the calculation method is carried out, the capacitor bank capacity is 15 MVAr. The simulation results with Matlab Simulink R2016a output voltage is 150 kV, current is 4500 A and power factor is 0.94 lagging. Keywords: Electric Power System, Capacitor Bank, Matlab Simulink R2016a.